Olmsted syndrome: Report of two cases - G K Tharini; N Hema; S Jayakumar; B Parveen (Wolters Kluwer Medknow Publications, 2011)
Olmsted syndrome is an uncommon genetic disorder with symmetrical, diffuse, transgredient, mutilating palmoplantar keratoderma and periorificial hyperkeratosis. Olmsted syndrome in a female patient is particularly rare, and we report two unrelated female patients of Olmsted syndrome, who presented with perioral hyperkeratosis and palmoplantar keratoderma. One of our patients also had woolly hair from birth and flexion contracture of a digit, while the other had pseudoainhum. There was no cardiac involvement. Hence, the diagnosis of Olmsted syndrome was made.